Peningkatan Antusiasme Belajar Anak Desa Sidorejo Melalui Program Bimbingan Belajar Sore - Jessica Anisa Pratama; Siti Azizah Susilawati; Ari Widayanti; Khusniyati Masykuroh (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
Education is a key factor in human resource development, especially in rural areas that often face challenges in accessing quality education. The Afternoon Tutoring Program (Bimbel Sore) conducted by KKN-MAS students from Universitas Muhammadiyah Prof. Dr. HAMKA in Sidorejo Village aims to enhance elementary school students' academic understanding and learning motivation. This program was attended by 30 students and focused on core subjects such as Mathematics, Indonesian Language, and Natural Sciences using an interactive approach, including group discussions, quizzes, and Q&A sessions. Evaluation results showed an increase in students' comprehension, with an average score improvement of 25%, as well as greater active participation in learning. Furthermore, the program contributed to boosting students' confidence in facing academic challenges. This initiative is expected to serve as a model for improving education quality in rural areas and inspire other community service activities. The sustainability of this program can be strengthened by involving more volunteers and expanding the range of taught materials to better align with students' needs in the future.